A chirality‐dependent action of vitamin C in suppressing Kirsten rat sarcoma mutant tumor growth by the oxidative combination: Rationale for cancer therapeutics. Issue 10 (8th October 2019) - Wu, Xinggang; Park, Mikyung; Sarbassova, Dilara A.; Ying, Haoqiang; Lee, Min Gyu; Bhattacharya, Rajat; Ellis, Lee; Peterson, Christine B.; Hung, Mien‐Chie; Lin, Hui‐Kuan; Bersimbaev, Rakhmetkazhi I.; Song, Min Sup; et al.
Abstract : Kirsten rat sarcoma (KRAS) mutant cancers, which constitute the vast majority of pancreatic tumors, are characterized by their resistance to established therapies and high mortality rates. Here, we developed a novel and extremely effective combinational therapeutic approach to target KRAS mutant tumors through the generation of a cytotoxic oxidative stress. At high concentrations, vitamin C (VC) is known to provoke oxidative stress and selectively kill KRAS mutant cancer cells, although its effects are limited when it is given as monotherapy. We found that the combination of VC and the oxidizing drug arsenic trioxide (ATO) is an effective therapeutic treatment modality. Remarkably, its efficiency is dependent on chirality of VC as its enantiomer d ‐optical isomer of VC (d ‐VC) is significantly more potent than the natural l ‐optical isomer of VC. Thus, our results demonstrate that the oxidizing combination of ATO and d ‐VC is a promising approach for the treatment of KRAS mutant human cancers. Abstract : What's new? A new combination therapy could effectively fight Kirsten rat sarcoma (KRAS)‐mutant cancers. Although KRAS mutations frequently crop up in human cancers, therapies targeting them have proved difficult to find. In our study, the authors tested a novel approach to kill the cancer cells by inducing oxidative stress with vitamin C and arsenic trioxide. The combo successfully killed cancer cells, with one surprising twist. When the researchers tested the therapy in a mouse xenograft model, they found that the tumor‐shrinking action depended on the chirality of the vitamin C molecule. The D isomer showed much greater efficacy than the naturally occurring L isomer.